2020
DOI: 10.1016/j.psj.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Carcass characteristics, chemical composition, physicochemical properties, texture, and microstructure of meat from spent Pekin ducks

Abstract: The aim of the study was to compare P33 (Polish Pekin), P8 (Danish Pekin), and LsA (English Pekin) ducks after 2 reproductive seasons for carcass composition and some meat quality traits. A total of 48 duck carcasses (8 male carcasses and 8 female carcasses of each genotype) were studied. Whole carcasses were dissected, and pH and electrical conductivity of the breast and leg muscles were determined 24 h postmortem. After dissection, breast and leg muscles were sampled to determine proximate composition, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
(14 reference statements)
6
7
0
Order By: Relevance
“…Also, we observed that total protein content gradually decreased above 38 days of age. The results of the present study are similar to those of Kokoszyński et al. (2020) , who demonstrated that the protein content of breast muscle in Pekin duck was reduced after seven weeks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, we observed that total protein content gradually decreased above 38 days of age. The results of the present study are similar to those of Kokoszyński et al. (2020) , who demonstrated that the protein content of breast muscle in Pekin duck was reduced after seven weeks.…”
Section: Discussionsupporting
confidence: 91%
“… Kokoszyński et al. (2019 ; 2020 ) revealed that potassium, iron, cooking loss and protein contents in the breast muscles increase with age in Polish Peking ducks. The lactate and anserine contents also increased with age, whereas the amount of fumarate, betaine, taurine, inosine, and alkyl-substituted free amino acids decreased ( Liu et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The compared strains of Pekin duck did not differ in chemical composition of thighs. Other authors investigated chemical composition of different strains of Pekin ducks and found that genetics in uenced the contents of moisture, protein, lipid and collagen in breasts and thighs [10,33,34,35]. Moreover, in our study, housing system did not affect the chemical composition of duck meat, as also was con rmed by Michalczuk et al [36] for Pekin duck and Michalczuk et al [37] for Muscovy duck.…”
Section: Chemical Characteristics Of Meatsupporting
confidence: 84%
“…From the start of the study, animals were fed with the same diets that were formulated to meet the maintenance and growth requirements of animals [14] (Table 1). Diets fed from days 1 to 49 were starter (days 1-21), grower (days [22][23][24][25][26][27][28][29][30][31][32][33][34][35] and nisher (days [36][37][38][39][40][41][42][43][44][45][46][47][48][49]. All components of the diets were analyzed for dry matter [15], crude protein [16], crude fat [17], crude ber [18], calcium [19], and phosphorus [20] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the breast muscles of King pigeons showed significantly higher electrical conductivity values measured 24 h postmortem compared to the EC 24 values of the breast muscles from carrier pigeons. EC 24 values for the breast muscle of the studied pigeons were lower than in six-week-old broiler chickens [ 35 ], and higher than in 112-week-old Pekin ducks [ 36 ].…”
Section: Discussionmentioning
confidence: 99%